Enhancing the tourism industry in the Lenggong Valley via a mindfulness approach - Ganesan, Vithya; Mohamed, Ramli; Khor , Yoke Lim; Md Noor, Shuhaida (2013)
Tourism destinations should be planned and designed to play a role in enhancing the state of mindfulness among visitors. Mindfulness refers to a state of mind of visitors who are actively engaged with the surroundings in processing information and is associated with greater learning and satisfaction. This paper will suggest how tourism destinations can be promoted and can enhance visitors’ positive attitudes, appreciation and empathy towards the sites they visit. Ultimately, mindfulness can induce them to develop a sense of attachment and stewardship towards the conservation of the places they visit. Learning theories and communication factors will be used to formulate a strategic perspective for the mindfulness approach to result in creating tourists with more knowledge, satisfaction and a higher level of understanding and interpretation towards the Lenggong Valley. In the final analysis, this paper assesses the challenges and processes of how tourism products, as in the case of the Lenggong Valley archaeological sites, can be narrated, interpreted and presented in a manner which can inculcate mindful tourists and induce them, in turn, to assist in the promotion of sustainable tourism in the area.